East Slavic Lexeme Graduśnik (“Thermometer”) in Dialects and History of the Polish Language - Jaros, Irena (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
On the basis of Polish and East Slavic historical and dialect sources, the author discusses the genesis, history, and extent of the lexem graduśnik (“thermometer”) in the Polish language. It is the East Slavic loanword that appeared in the colloquial Polish language in the North-Eastern borderland and in some Polish dialects in the 19th century. It has never surfaced in the literary Polish language. It would always be considered a linguistic mistake. In Polish dialects, the lexeme was noted in Mazovia and Lesser Poland.